Bonus issue announcements and its impact on share prices of colombo stock exchange (cse) in sri lanka - Ramesh, S.; Nimalathasan, B. (University of Jaffna, 2011)
Over the year‟s bonus issues announcements and share prices have been subjected to many empirical discussions within the finance literatures. To the knowledge of the researchers very few studies have attempted to observe bonus issue announcement and share prices in Sri Lanka. In attempt to fill this research gap the present study was initiated to find out the impact of bonus issue announcements on share prices. Primary information and secondary data were collected from Colombo Stock Exchange (CSE). The present study used the „standard-event study methodology‟ to examine the impact of bonus issues announcement on share prices. The study was identified sixty-seven events (32 Companies) listed in the CSE for the period from year 2003 to 2007. These sixty-seven events are divided into financial sector and non financial sector. Several interrelated procedures are performed through t-test by the researchers during the data analysis procedures. Operational hypotheses were formulated and results revealed that 43% of Abnormal Returns (ARs) are positively and 57% of ARs are negatively on the event day “0” (announcement day). In addition the bonus issue announcements have insignificant impact on share price of the CSE i.e., 5% level or 10% level of level of significance. Outcomes of the study will be useful to the academicians, practitioners, policy makers and investors for making suitable policy formulations for the companies. Further the companies are able to decide a suitable polices in executing their financial decision without harming to the market value of the shares.
Keywords: Bonus issue announcements; Share prices; Colombo stock exchange (CSE)